Radical verstehen necessary (Historia, 2021)
The computer revolution of the second half of the twentieth century was perhaps the major technological development that asserted an influence on the discipline of history. Almost all facets of scientific activity which historians resort to, have been affected directly in some way or another by computer technology. There are even rumours that the silicon brain can do certain things better than the historian.
Keywords: silicon brain; History; Historian; technological development; twentieth century